Low-level laser efficiency in the therapy of chronic gingivitis in children - Igić Marija; Kesić Ljiljana; Apostolović Mirjana; Kostadinović Ljiljana (Vojnosanitetski Pregled)
Background/Aim. Gingivitis is a frequent phenomenon in children considered to be a risk factor for the occurrence and progression of paradontal tissue disease. So, it is necessary not only to identify inflammation, but also to react in due time and adequately in order to avoid further disease spread and the beginning of periodontitis. The aim of this study was to determine the efficiency of a low-level laser application in the therapy of chronic gingivitis in children. Methods. The study a included hundred of children with permanent dentition suffering from chronic gingivitis. All the examinees were divided into two groups: group I - 50 examinees with chronic gingivitis, who underwent the basic therapy; group II - 50 examinees with chronic gingivitis, who underwent the basic therapy and also a therapy with a low-level laser. Evaluation of the condition of oral hygiene, the health of gingiva and periodontium were done using appropriate index before and after the therapy. Results. For the plaque index (PI) following results were obtained: in the group I PI = 1.94, and in the group II PI = 1.82. After the therapy in both groups PI was 0. In the group I sulcus plaque index (SPI) was 2.02 before the therapy and 0.32 after the therapy. In the group II SPI was 1.90 before the therapy, and 0.08 after the therapy. In the group I Community Periodontal Index of Treatment Needs (CPITN) was 1.66 before the therapy, and 0.32 after the therapy, and in the group II CPITN was 1.60 before the therapy, and 0.08 after the therapy. Conclusion. Chronic gingivitis in children can be successfully cured by the basic treatment. The use of a low-level laser can significantly improve this effect.